Pengetahuan Gizi Ibu Sebagai Determinan Stunting di Jawa Barat: Disparitas Perdesaan-Perkotaan: Pengetahuan Gizi Ibu Sebagai Determinan Stunting di Jawa Barat: Disparitas Perdesaan-Perkotaan - Anna Vipta Resti Mauludyani; Ali Khomsan (Amerta Nutrition, 2022)
Background: Maternal nutritional knowledge must be strengthened to lower the problem of stunting. However, there is currently a lack of information regarding the nutritional knowledge of mothers of stunted and non-stunted children in West Java's rural and urban areas. Objectives: This study compares the nutritional knowledge of mothers of under-five children in West Java across four groups: those who are stunted in rural areas (SR), those who are stunted in urban areas (SU), and those who are not in rural (NR) and urban (NU). Methods: This cross-sectional study was conducted in Cianjur (rural) and Sukabumi City (urban) in June 2022. Data was collected through interview to 300 mothers of children underfive using pretested questionnaire. Nutritional knowledge comprised of 20 questions about infant and young child feeding and balanced nutrition. One-way ANOVA and Tukey HSD Post Hoc Tests were applied for data analyses using IBM SPSS 22.0. Results: Overall, both prevalence of stunting in rural and urban was 33.3% and 30.7%, respectively. Mothers in four groups had moderate nutritional knowledge, with total scores ranging from 70.9 to 75.2. Mothers of NU were found to have more nutritional awareness than NR and SR. In comparison to NR, mothers of NU babies are more likely to be aware that their 2- or 3-month-old infants cannot consume bananas or papayas. Compared to SR, more NU mothers are aware that vegetables do not contain protein. There are more mothers of NU know that sweetened condensed milk is not more nutrient rich compared to powder or liquid milk than NR and SR. Conclusions: Urban mothers have superior nutritional knowledge than rural mothers. Even, knowledge of rural mother with stunted child is the poorest. With the high prevalence of stunting, access to nutritional information should be enhanced, with a focus on the feeding practices of young children.